50 Shades of Radicalism: an Analysis of Contemporary Radical Parties in Europe - Bartoszewicz, Monika Gabriela (International Studies. Interdisciplinary Political and Cultural Journal, 2015)
The paper provides a comprehensive overview of European radical parties. The main aim of this paper is to examine whether there are common patterns regarding these parties, and to analyse the implications of this phenomenon. In order to achieve the above, the paper proceeds as follows: Firstly, the phenomenon of political radicalisation in contemporary Europe is explored. This leads to mapping the radical political landscape in Europe. Finally, the paper concludes with the analysis of the possible outcomes of radicalisation of European politics including the possible societal effects. By doing so the paper argues that a fresh theoretical approach to comprehend the phenomenon is necessary.